2012
DOI: 10.1364/oe.20.00b428
|View full text |Cite
|
Sign up to set email alerts
|

737 Tb/s (96 x 3 x 256-Gb/s) mode-division-multiplexed DP-16QAM transmission with inline MM-EDFA

Abstract: Transmission of a 73.7 Tb/s (96x3x256-Gb/s) DP-16QAM mode-division-multiplexed signal over 119km of few-mode fiber transmission line incorporating an inline multi mode EDFA and a phase plate based mode (de-)multiplexer is demonstrated. Data-aided 6x6 MIMO digital signal processing was used to demodulate the signal. The total demonstrated net capacity, taking into account 20% of FEC-overhead and 7.5% additional overhead (Ethernet and training sequences), is 57.6 Tb/s, corresponding to a spectral efficiency of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(39 citation statements)
references
References 4 publications
(4 reference statements)
0
39
0
Order By: Relevance
“…The total capacity challenge in MDM transmissions were conducted as 57.6 Tb/s [84,85] and recently at 115.2 Tb/s [86].…”
Section: Mode-division Multiplexing Transmissionmentioning
confidence: 99%
“…The total capacity challenge in MDM transmissions were conducted as 57.6 Tb/s [84,85] and recently at 115.2 Tb/s [86].…”
Section: Mode-division Multiplexing Transmissionmentioning
confidence: 99%
“…Many experiments have validated the high throughput achievable by SDM. Some remarkable cases are the 2.15 Pb/s transmission over 31 km employing a 22 multi-core single mode fiber [9] or the 57.6 Tb/s over 119 km employing a few-mode fiber (FMF) [10]. Further reading and a thorough review of different SDM transmission records can be found at [11].…”
Section: Space Division Multiplexingmentioning
confidence: 99%
“…Mode Division Multiplexing (MDM) whereby selective mode excitation and detection schemes are used to define distinguishable information channels within a few mode fiber (FMF) [1,2] is gathering increasing interest as a cost effective means to accommodate the anticipated future (exponential) growth in internet traffic. Rapid progress has been made in the development of FM transmission fibers and optical amplifiers and a record data transmission capacity of 73.7Tb/s has recently been demonstrated over a 110km length link of three-mode fiber (3MF) incorporating an inline 3M-EDFA [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid progress has been made in the development of FM transmission fibers and optical amplifiers and a record data transmission capacity of 73.7Tb/s has recently been demonstrated over a 110km length link of three-mode fiber (3MF) incorporating an inline 3M-EDFA [2]. A longer transmission distance of 700km has been reached at an aggregate linerate of 1.7Tb/s in 3MF recirculating loop experiments [3].…”
Section: Introductionmentioning
confidence: 99%